Tanggung Jawab dan Wewenang Notaris/PPAT terhadap Kekeliruan dan Pembatalan Akta Jual Beli Tanah - Yogi Kristanto; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Fakultas Hukum, Universitas Warmadewa, 2020)
Notary as the Land Deed Official is an additional authority granted by law to carry out legalization of legal binding by the community, especially in the land sector. Therefore, the notary’s authority as the Land Deed Making Official is not to make any mistake in issuing an authentic deed which results in the cancellation of the agreement made. This study discusses two issues: the liability and authority of the Notary as the official for making land deed if a mistake or cancellation of the land sale and purchase certificate occurs and the legal consequences if it has taken place. The research method used in this research is normative legal research method. The results of the research show that the liability of the Notary as the Land Deed Making Official for his / her mistakes is in the form of civil liability in the form of material and immaterial compensation, criminal liability in the form of imprisonment of at least 6 years and a maximum of 8 years, and administrative liability in the form of written warning to disrespect dismissal. The legal consequence is that the Notary’s license as a Land Deed Official can be revoked and the land deed he has made can be canceled or null and void.